2000
DOI: 10.1002/1520-6300(200009/10)12:5<702::aid-ajhb15>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends for takeoff and maximum adolescent growth for eight decades of Japanese cohort data

Abstract: The presence of secular trends in the onset or takeoff of the adolescent growth spurt and subsequent adolescent growth of Japanese boys and girls were investigated using data published in "The Statistical Report of the School Health Survey" by the Ministry of Education, Science, Sports and Culture, Japan. An optimum kernel regression method was used to derive the biological parameters of the adolescent growth curve. An increasing trend in height at takeoff (i.e., height at the onset of the adolescent growth sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A decline in estimated mean ages at PHV among Danish youth born in the 1930s through the 1960s, 12.5 to 12.0 years in girls and 14.5 to 14.2 years in boys, was recently reported [61]. Ages at PHV did not differ among boys and girls in the Fels Longitudinal Study born in the 1960s, 1970s and 1980s [62], while ages at PHV among Japanese youth born in the 1960s through early 1980s changed negligibly [63,64].…”
Section: Discussionmentioning
confidence: 94%
“…A decline in estimated mean ages at PHV among Danish youth born in the 1930s through the 1960s, 12.5 to 12.0 years in girls and 14.5 to 14.2 years in boys, was recently reported [61]. Ages at PHV did not differ among boys and girls in the Fels Longitudinal Study born in the 1960s, 1970s and 1980s [62], while ages at PHV among Japanese youth born in the 1960s through early 1980s changed negligibly [63,64].…”
Section: Discussionmentioning
confidence: 94%
“…Ali et al (2000) studied secular changes in Japanese leg length for birth cohorts from 1943 to 1978, showing a steep rise in leg length as a percentage of height from 1943 to 1968 but a plateau thereafter. In addition they showed that this percentage increased with age until puberty, i.e., 13 years in boys and 11 years in girls, and then either stabilized (girls) or fell slightly (boys).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the secular trend can be decomposed into three separate components. The technique represents an extension of the approach by Ali, Lestrel, and Ohtsuka (2000) who analyzed growth curves of Japanese height over eight decades using kernel regression, and identified turning points on the curves reflecting age at take‐off and age at peak velocity.…”
Section: Introductionmentioning
confidence: 99%
“…We first confirmed the adolescent growth spurt characteristics in Japanese children according to Ali et al .., using data from The Statistical Report of the School Health Survey by the Ministry of Education, Science, Sports and Culture, Japan and then, on the basis of the criteria defined by Aksglaede et al ., we calculated the participants' age at peak height velocity (APHV). We calculated the height velocity from the first grade of elementary school (6–7 years of age) to graduation from junior high school (14–15 years of age); height velocity was defined as the difference in the heights recorded for 2 adjacent years.…”
Section: Methodsmentioning
confidence: 99%